1996
DOI: 10.1103/physrevb.53.957
|View full text |Cite
|
Sign up to set email alerts
|

Influence of gradient corrections on the bulk and surface properties ofTiO2andSnO2

Abstract: First-principles calculations based on density functional theory and the pseudopotential method have been used to investigate the influence of gradient corrections to the standard LDA technique on the equilibrium structure and energetics of rutile TiO 2 and SnO 2 perfect crystals and their (110) surfaces.We find that gradient corrections increase the calculated lattice parameters by roughly 3 %, as has been found for other types of material. Gradient corrections give only very minor changes to the equilibrium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
70
2
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 175 publications
(88 citation statements)
references
References 39 publications
15
70
2
1
Order By: Relevance
“…Our energies are lower because we have included gradient corrections to the exchange-correlation energy, which have been shown to lower calculated oxide surface energies. 7 We note in passing that Ramamoothy et al demonstrated that the ͑110͒ surface energy converges slowly with slab thickness, and oscillates with odd and even numbers of layers. However, our choice of system size is constrained by other considerations which we discuss below.…”
Section: A the Stoichiometric Surfacementioning
confidence: 99%
See 2 more Smart Citations
“…Our energies are lower because we have included gradient corrections to the exchange-correlation energy, which have been shown to lower calculated oxide surface energies. 7 We note in passing that Ramamoothy et al demonstrated that the ͑110͒ surface energy converges slowly with slab thickness, and oscillates with odd and even numbers of layers. However, our choice of system size is constrained by other considerations which we discuss below.…”
Section: A the Stoichiometric Surfacementioning
confidence: 99%
“…23 Relaxation of the ions to mechanical equilibrium, in which the ionic forces were generally less than 0.2 eV Å Ϫ1 , was achieved by the conjugate-gradients minimization of the total energy with respect to the ionic positions. Recent results 7 indicate that gradient corrections to the local-density approximation can have a large effect on oxide surface energies, and accordingly we have employed the generalizedgradient approximation ͑GGA͒ of Perdew and Wang 24 in all our calculations.…”
Section: Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…[36][37][38][39][40][41][42][43][44][45][46] It should be noted, however, that many of these simulations are based on structural models characterized by either point group or translational symmetry constraints. Semiempirical tight-binding studies based on cluster models by Goniakowski et al and Bredow et al show favorable dissociative adsorption at all coverages, [36][37][38] as do some early first-principles Hartree-Fock (HF) and density functional theory (DFT) studies.…”
Section: Introductionmentioning
confidence: 99%
“…Semiempirical tight-binding studies based on cluster models by Goniakowski et al and Bredow et al show favorable dissociative adsorption at all coverages, [36][37][38] as do some early first-principles Hartree-Fock (HF) and density functional theory (DFT) studies. 39,40 A first-principles molecular dynamics (MD) study by Lindan et al, 47 using the generalized gradient approximation (GGA), employed a periodic slab approach to show that dissociation of water leads to stabilization at low coverages. In these calculations, all adsorbates are subject to symmetry constraints, so neighboring molecules are restricted to be at fixed orientation and separation.…”
Section: Introductionmentioning
confidence: 99%